IPSC-derived organ-on-a-chip models for personalized human genetics and pharmacogenomics studies. Issue 4 (April 2023) - Palasantzas, Victoria E.J.M.; Tamargo-Rubio, Isabel; Le, Kieu; Slager, Jelle; Wijmenga, Cisca; Jonkers, Iris H.; Kumar, Vinod; Fu, Jingyuan; Withoff, Sebo
Highlights: Organ-on-a-chip (OoC) technology combined with iPSC and clustered regularly interspaced short palindromic repeat (CRISPR) technology enables modeling of complex genetic diseases and environmental factors such as the microbiome. By creating and combining multiorgan and patient-specific models, genetic variants, and risk scores can be validated to facilitate the translation of associative findings to biological models. OoC models provide an improved environment that mimics physiological cell- to organ-level interactions. The genetic background of disease can be studied at the multiorgan level by generating OoC models from iPSC lines. OoCs will soon be used to study human (patho)physiology, pharmacogenetics, and drug discovery, which may reduce animal testing and accelerate translation. Abstract: Genome-wide association studies (GWAS) have now correlated hundreds of genetic variants with complex genetic diseases and drug efficacy. Functional characterization of these factors remains challenging, particularly because of the lack of human model systems. Molecular and nanotechnological advances, in particular the ability to generate patient-specific PSC lines, differentiate them into diverse cell types, and seed and combine them on microfluidic chips, have led to the establishment of organ-on-a-chip (OoC) platforms that recapitulate organ biology. OoC technology thus provides unique personalized platforms for studying the effects of host genetics and environmental factors on organ physiology. In this review we describe the technology and provide examples of how OoCs may be used for disease modeling and pharmacogenetic research.